Bioaerosol Sampling in Clinical Settings: A Promising, Noninvasive Approach for Detecting Respiratory Viruses. (26th December 2016) - Nguyen, Tham T.; Poh, Mee K.; Low, Jenny; Kalimuddin, Shirin; Thoon, Koh C.; Ng, Wai C.; Anderson, Benjamin D.; Gray, Gregory C.
Abstract: Background: Seeking a noninvasive method to conduct surveillance for respiratory pathogens, we sought to examine the usefulness of 2 types of off-the-shelf aerosol samplers to detect respiratory viruses in Singapore. Methods: In this pilot study, we ran the aerosol samplers several times each week with patients present in the patient waiting areas at 3 primary health clinics during the months of April and May 2016. We used a SKC BioSampler with a BioLite Air Sampling Pump (run for 60 min at 8 L/min) and SKC AirChek TOUCH personal air samplers with polytetrafluoroethylene Teflon filter cassettes (run for 180 min at 5 L/min). The aerosol specimens and controls were studied with molecular assays for influenza A virus, influenza B virus, adenoviruses, and coronaviruses. Results: Overall, 16 (33.3%) of the 48 specimens indicated evidence of at least 1 respiratory pathogen, with 1 (2%) positive for influenza A virus, 3 (6%) positive for influenza B virus, and 12 (25%) positive for adenovirus. Conclusions: Although we were not able to correlate molecular detection with individual patient illness, patients with common acute respiratory illnesses were present during the samplings. Combined with molecular assays, it would suggest that aerosol sampling has potential as a noninvasive method for novel respiratory virus detection in clinical settings.